Dark Triad in the context of career choice - Čopková, Radka; Jendrejáková, Annamária (Sociální pedagogika, 2020)
The research study deals with Dark Triad traits (Machiavellianism, narcissism, psychopathy) in the context of the vocational interests in high school students. We assumed that students tending towards the helping professions might score differently in Dark Triad traits compared to students oriented towards professions such as manufacturing, business, or law (Jonason et al., 2014; Kowalski et al., 2017). The main goal of the study was to examine the differences in Dark Triad traits with respect to students´ professional intentions. The research was conducted on a sample of 181 students of grammar schools and secondary vocational schools in Slovakia (Mage = 18.3 years; SD = .77); 57% were boys, 43% were girls. The Slovak version of the Short Dark Triad (Čopková Šafár, 2020; Jones Paulhus, 2014) and the Questionnaire of Professional Intentions (Džuka, 2006) were used. Testing the significance of differences between students with different professional intentions pointed to significant differences in subclinical psychopathy. Significantly higher psychopathy was shown by students oriented to the sphere of production compared to students oriented to art, science and education. Also in psychopathy, students oriented towards the sphere of business scored higher than students oriented towards the sphere of art and education. Testing of within-subject variability showed Machiavellianism as the most significant feature of the Dark Triad in all professional spheres.